2019
DOI: 10.2215/cjn.09550818
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cinacalcet Prescription across US Hemodialysis Facilities

Abstract: Background and objectives Calcimimetic drugs used to treat secondary hyperparathyroidism are being considered for inclusion in the Medicare ESRD Prospective Payment System bundle after an evaluation period. Understanding of utilization patterns of calcimimetics across dialysis facilities may help align financial incentives with clinical objectives. Our study's purpose was to describe the distribution of cinacalcet prescription across United States hemodialysis facilities and to explore factors that may influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…21 Another possibility is that genetic differences could influence the ability to control PTH levels in different racial groups. Recent work by Fuller et al 22 has shown higher PTH levels despite greater cinacalcet use among black/ African American versus non-black/African American US HD patients. Further studies are needed to determine whether inherited or other factors explain higher PTH levels among US black/African American patients and how such factors may affect therapeutic approaches to improve PTH management and ultimately minimize consequent bone and cardiovascular complications.…”
Section: Discussionmentioning
confidence: 98%
“…21 Another possibility is that genetic differences could influence the ability to control PTH levels in different racial groups. Recent work by Fuller et al 22 has shown higher PTH levels despite greater cinacalcet use among black/ African American versus non-black/African American US HD patients. Further studies are needed to determine whether inherited or other factors explain higher PTH levels among US black/African American patients and how such factors may affect therapeutic approaches to improve PTH management and ultimately minimize consequent bone and cardiovascular complications.…”
Section: Discussionmentioning
confidence: 98%
“…At the aggregate level, the patient characteristics and given previous research that has identified an association between vintage and cinacalcet utilization. 10 Although prior studies have identified an association between these baseline characteristics and calcimimetic use, this analysis is (to our knowledge) the first time the 100% sample of the Medicare Part B claims has been utilized (1) to describe variation in both cinacalcet and etelcalcetide utilization and (2) to assess utilization patterns of calcimimetics in the Medicare population during the TDAPA period for both these therapies.…”
Section: Discussionmentioning
confidence: 99%
“…8 More frequent monitoring may be required for patients with SHPT who are treated with calcimimetics to reach their target maintenance dose. 9 10,11 The dialysis facility identifier listed on each beneficiary's first observed maintenance dialysis claim in 2018 was captured from the Part B claims and cross-referenced to the current CMS Dialysis Facility Compare public use files. 12 For each dialysis provider, the following…”
Section: Data Source and Variablesmentioning
confidence: 99%
“…While this pragmatic approach may be seen as ethically disturbing since it heavily impacts on a clinical choice, it also underlines the potential strength of scientific societies in the discussion on treatment costs and availability, which in turn influence clinical choices [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The way dialysis is reimbursed plays an important role, since the intravenous drugs administered during the dialysis session are usually part of the dialysis budget (dialysis "bundle") and previous experience with erythropoietin clearly shows that the method of reimbursement deeply affects clinical practice [34][35][36][37][38][39]. Conversely, oral drugs are usually outside the dialysis budget, and this is frequently the case for first generation oral calcimimetic agents.…”
Section: Introductionmentioning
confidence: 99%